Creating opportunities through mentorship, parental involvement, and safe spaces (COMPASS) program: multi-country study protocol to protect girls from violence in humanitarian settings. - Falb, Kathryn L; Tanner, Sophie; Ward, Leora; Erksine, Dorcas; Noble, Eva; Assazenew, Asham; Bakomere, Theresita; Graybill, Elizabeth; Lowry, Carmen; Mallinga, Pamela; Neiman, Amy; Poulton, Catherine; et al. (BMC public health, 2016)
Violence against adolescent girls in humanitarian settings is of urgent concern given their additional vulnerabilities to violence and unique health and well-being needs that have largely been overlooked by the humanitarian community. In order to understand what works to prevent violence against adolescent girls, a multi-component curriculum-based safe spaces program (Creating Opportunities through Mentorship, Parental involvement and Safe Spaces - COMPASS) will be implemented and evaluated. The objectives of this multi-country study are to understand the feasibility, acceptability and effectiveness of COMPASS programming to prevent violence against adolescent girls in diverse humanitarian settings.